Kajian Kelayakan Finansial Fotovoltaik Terintegrasi On Grid Dengan Kapasitas 20 kWp - Muchamad Nur Qosim; Rinna Hariyati (KILAT, 2021)
ABSTRACT Entering the 21st century, oil and gas supplies are running low. While the need for energy is increasing, especially in industrialized countries, it will increase to 70% between 2000 and 2030. In 2017, the electricity needs will reach 25.4 trillion kWh. Solar energy that can be generated for the entire Indonesian mainland which has an area of ​​± 2 million km2 with a radiation distribution of 4.8 kWh/m2/day is 5.10 mW, equivalent to 112,000 gWp. Investment costs include the costs of purchasing all required solar power plant components, such as the cost of purchasing solar modules and purchasing an inverter. Obtained the Internal Rate of Return (IRR) is more than the interest rate, which is 27.11% and it can be concluded that the planning of the on-grid solar power plant in the 20 KWP capacity system can be said to be feasible. Keyword: Solar Cell, investment, electrical Energy ABSTRAK Memasuki abad 21, persediaan minyak dan gas bumi semakin menipis. Sementara kebutuhan akan energi semakin meningkat, utamanya di negara-negara industri akan meningkat sampai 70% antara tahun 2000 sampai dengan 2030. Pada tahun 2017, kebutuhan energi listrik mencapai 25,4 trilyun kWh. Energi surya yang dapat dibangkitkan untuk seluruh daratan Indonesia yang mempunyai luas ±2 juta km2 dengan distribusi penyinaran sebesar 4,8 kWh/m2/hari adalah sebesar 5,10 mW atau setara dengan 112.000 gWp. Biaya investasi mencakup mengenai biaya pembelian semua komponen pembangkit listrik tenaga surya yang dibutuhkan, seperti biaya pembelian modul surya dan pembelian inverter. Diperoleh Internal Rate of Return (IRR) lebih dari tingkat suku bunga, yaitu 27,11% dan dapat disimpulkan bahwa perencanaan PLTS on-grid di system kapasitas 20 KWP ini dapat dikatakan layak. Kata kunci: Cel surya, investasi, Energi listrik